Clinical case of the treatment of acute heart failure with extracorporeal membrane oxygenation in patients with acute idiopathic giant cell myocarditis - B.M. Todurov; G.I. Kovtun; A.N. Postupalsky; A.N. Druzhyna; O.A. Loskutov; I.N. Kuzmich; А.О. Shpachuk (Кардіохірургія та інтервенційна кардіологія)
The article describes clinical case demonstrating the feasibility of using extracorporeal circulatory support in patients with severe heart failure caused by idiopathic giant cell myocarditis. Extracorporeal membrane oxygenation, conducted over 15 days, resulted in increase left ventricular ejection fraction of 18 % to 30 %, reduction and complete cancellation of the inotropic support. Echocardiographic study showed a significant decrease in heart size (end-diastolic volume – from 100 to 90 ml, end-systolic volume – from 85 to 60 ml), as well as a reduction of the right ventricular systolic pressure from 40 to 30 mm Hg. Thus, extracorporeal membrane oxygenation is a completely justified and effective method for stabilizing hemodynamics in patients with acute idiopathic giant cell myocarditis.